Traveling Wave Solutions for the Nonlinear Fractional Sharma-Tasso-Olever Equation - Lu, Dianchen; Ye, Mengyang (International Journal of Mathematical Research, 2017)
In this paper, the generalized exp(-Φ(ξ))-expansion method along with the Jumarie’s modified Riemann-Liouville derivatives is proposed to solve the nonlinear fractional Sharma-Tasso-Olever (STO) equation. Consequently, the exact solutions are obtained in terms of the trigonometric, exponential, hyperbolic, and rational functions, which confirm the proposed technique is very effectual and easily applicable.